Associations between Swiss Needle Cast Severity and Foliar Nutrients in Young-Growth Douglas-Fir in Coastal Western Oregon and Southwest Washington, USA. Issue 5 (10th May 2019) - Lan, Yung-Hsiang; Shaw, David C; Ritóková, Gabriela; Hatten, Jeff A
Abstract: Swiss needle cast (SNC) is a foliage disease of Douglas-fir ( Pseudotsuga menziesii ) caused by Nothophaeocryptopus gaeumannii, an ascomycete fungus (Mycosphaerellaceae) that causes tree growth reductions in the Pacific Northwest. The epidemiology of the fungus is generally well known, but the relations between disease expression and foliar nutrition are unclear. In this study, we used data from the Swiss Needle Cast Cooperative research and monitoring plot network in western Oregon and SW Washington to assess associations between SNC severity, carbon, and nine foliage nutrients (nitrogen, Na, K, P, Ca, Mg, Mn, Al, S). Foliage samples were collected from midcrown of selected Douglas-firs from each plot. SNC severity was determined on 2-year-old needles by multiplying disease incidence and fungal reproductive (pseudothecia) density. Disease severity and nutrient relations were determined using linear mixed models. SNC severity showed statistically significant positive trends with concentrations of carbon, nitrogen, Na, K, and S, no relation with concentrations of Ca, Mg, or Al, and slightly negative trends that were not significant for P and Mn. This is the first such analysis of associations between a conifer foliage disease and foliage nutrients across a landscape; subsequently, there is little published literature on how or why these nutrients may interact with disease.